Comparison of Treatment of Contractual Remedies under FIDIC 1999 Red and Yellow Books and UAE Contracts of Muqāwala - YOUSSEF, HOSSAM ELSHAHAT AZIZ MOHAMED (2017)
When a person enters into a contract with another, both contracting parties are obliged, by contract and by law, to fulfill their respective obligations in accordance with that contract. Either party may, however, fail to carry out, not be able to or decide not to, perform any or all of its contractual obligations, hence it is considered that contract is breached by the defaulting party. The questions then arise: what are the respective obligations of the contracting parties, both under contract and at law? What forms of remedies are available to the aggrieved party to obtain redress or relief? This study first introduces briefly, the core contractual obligations of the employer and the contractor against each other under FIDIC forms of contract as found in the FIDIC Red and Yellow Books on the one hand, and the UAE Civil Law, in particular the Muqāwala provisions, on the other. Thereafter it goes on to the main focus of the research, namely the nature of the contractual remedies available to an aggrieved party where there has been a breach of contract. In this research, various remedies are examined within the UAE Civil Law, as the governing law related to construction contracts , and the FIDIC Suite of Contracts, as the most common standard form suite of engineering and construction contracts used for construction projects in the UAE and internationally. The primary purpose of the study is to assist employers, contractors, engineers, lawyers, international financing organizations and stakeholders in construction projects, using FIDIC forms of contract subject to the UAE Civil Law as the applicable law, to better understand the courses of action available to a contracting party when the contractual obligations of the other party are not complied with. Since most of the legal systems of the Arab Middle Eastern countries are founded upon Civil Law principles, it is envisaged that this research would support effective and efficient contract administration of construction projects within the region.